Neuroanatomy of executive functions, cognitive control processes and their interactions using functional magnetic resonance imaging - Fassbender, Catherine (Trinity College (Dublin, Ireland). School of Psychology, 2005)
Human behaviour, though appearing seamless, is comprised of a number of differing and interacting cognitive processes. In this dissertation I attempted to establish the anatomical networks subserving a number of different executive functions, which are crucial for normal human learning and behaviour with the use of functional magnetic resonance imaging (fMRI). These functions were the maintenance of task set, sustaining attentional focus, inhibition of prepotent responses and the detection of errors or situations in which an error is likely to occur.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin